2016
DOI: 10.1101/057794
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

DNA sequence properties that predict susceptibility to epiallelic switching

Abstract: Transgenerationally heritable epialleles are defined by the stable propagation of alternative transcriptional states through mitotic and meiotic cell cycles. Given that the propagation of DNA methylation at CpG sites, mediated in Arabidopsis by MET1, plays a central role in epigenetic inheritance, we examined genomewide DNA methylation in partial and complete loss-of-function met1 mutants. We interpreted the data in relation to transgenerational epiallelic stability, which allowed us to classify chromosomal ta… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…All six lines selected from top performing F 2 plants showed a reduction in enhanced growth by F 2:6 , further confirming the epigenetic nature of MSH1‐ derived growth changes, with similar dissipation patterns described previously in Arabidopsis ddm1 epiRILs (Cortijo et al ., ; Roux et al ., ). A recent study has suggested that stability and switching of acquired epigenetic states are influenced by DNA sequence composition and repetitiveness (Catoni et al ., ). It is also speculated that methylation variation not linked to a causal genetic variant tends to be less stable than when directly linked to genetic change (Schmitz et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…All six lines selected from top performing F 2 plants showed a reduction in enhanced growth by F 2:6 , further confirming the epigenetic nature of MSH1‐ derived growth changes, with similar dissipation patterns described previously in Arabidopsis ddm1 epiRILs (Cortijo et al ., ; Roux et al ., ). A recent study has suggested that stability and switching of acquired epigenetic states are influenced by DNA sequence composition and repetitiveness (Catoni et al ., ). It is also speculated that methylation variation not linked to a causal genetic variant tends to be less stable than when directly linked to genetic change (Schmitz et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…This is presumably attributed to losses of DNA and histone methylation that affect recruitment of CMT2, CMT3, and/or DRM2. The mechanistic basis for MET1 influencing non-CG methylation at some loci and not others is unknown, but a recent study identified that these sites are characterized by lower levels of repetitiveness and higher densities of CG motifs than sites where non-CG methylation does not depend on MET1 (Catoni et al, 2017).…”
Section: Met1 Methylation Is Dependent On Variant In Methylationmentioning
confidence: 99%
“…However, a clear functional role for gbM has yet to be identified although there have been a number of proposed functions such as regulation of expression and splicing (reviewed in Zilberman, 2017). The CG methylation in gbM genes is dependent on MET1, as it is lost in met1 mutants (Lister et al, 2008;Reinders et al, 2009;Teixeira et al, 2009;Stroud et al, 2013;Bewick et al, 2016;Catoni et al, 2017). Furthermore, upon reintroduction of wildtype MET1, most gbM is not restored, appearing only at a few loci after several generations of propagation following reintroduction of the wild-type allele (Reinders et al, 2009;Teixeira et al, 2009;Bewick et al, 2016;Catoni et al, 2017).…”
Section: Self-reinforcing Feedback Loops and Off-target Chromatin Modificationsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the transposition of a TE has been recently attributed as the cause to transgenerational abscisic acid insensitivity (Ito et al ). Further studies have revealed that sequence properties like low‐copy number loci with enrichment in CG dinucleotides are more likely to form transgenerationally stable epialleles (Catoni et al ). If so, the effect of TEs on the transgenerational inheritance of epialleles could be limited to TEs that have a low‐copy number in the genome.…”
Section: Transgenerational Nature Of Stress‐induced Epigenetic Modifimentioning
confidence: 99%